Development of Sanggabuana Coffee Product Innovation through Product Diversification: Case Study In Bumdes Buanamekar Business In Mekarbuana Village, Karawang - Sumarni, Neni; Suroso; Enjang Suherman (Media Wisata, 2023)
This study aims to determine the application of a diversification strategy with the development of innovation in Sanggabuana coffee products. This study used in-depth interviews, observation, and documentation studies and analyzed using technical and source triangulation. The study results were obtained to apply a diversification strategy focused on concentric diversification by producing new product outputs based on the raw material of KoSa as a coffee flavouring in desserts with the types of Pudding Kopi and Bolu Kopi, scrubs, and air fresheners. Furthermore, Bumdes can maximize e-commerce marketing.